Effectiveness of Mobile based Agro-Advisory Services in Addressing Information Need of the Stakeholders: A Case of m KRISHI® - Singh, Madan; Burman, R. Roy; Sharma, J. P.; Sangeetha, V.; Iquebal, Mir Asif (Indian Journal of Extension Education, 2015)
Many information and communication technology (ICT) projects in Indian agriculture have emerged, either substituting  or supporting extension services by providing access to agricultural information to the farmers, but its access to the  farmers in remote villages is restricted due to the lack of infrastructure. It creates information asymmetry among farmers.  Telecommunication, especially mobile phones have the potential to provide solution to the existing information  asymmetry in various lagging sectors like agriculture. mKRISHI® is one such project which made significant  contribution in information dissemination in some parts of India. The present study was undertaken for assessing its  effectiveness in information dissemination to the farmers in two districts of Maharashtra and Tamil Nadu where  mKRISHI® was working for the last six years. Data were collected from 60 respondents from the mKRISHI® member  farmers. The effectiveness was measured by effectiveness index developed for the purpose. The study revealed that the  extension services rendered by mKRISHI® were found to be highly effective by majority of the farmers (46.66 %).
Keywords: Effectiveness; Information need; mKRISHI® poverty; employment generation